Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1016/j.jvs.2010.04.085
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic acid inhibits oxidized LDL-mediated LOX-1 expression, ROS generation, and inflammation in human endothelial cells

Abstract: Findings from this study may provide insight into a possible molecular mechanism by which ellagic acid inhibits LOX-1-induced endothelial dysfunction. Our data indicate that ellagic acid exerts its protective effects by inhibiting NADPH oxidase-induced overproduction of superoxide, suppressing the release of NO by down-regulating iNOS, enhancing cellular antioxidant defenses, and attenuating oxLDL-induced LOX-1 up-regulation and eNOS down-regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
105
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(113 citation statements)
references
References 39 publications
8
105
0
Order By: Relevance
“…Previous studies have revealed apoptosis in VECs with elevated intracellular ROS levels [39,40]. Intracellular ROS levels are regulated by the balance between ROS generation and antioxidant enzymes [41]. Our results showed that elevated ROS levels induced by oxLDL were decreased significantly with PT pretreatment.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have revealed apoptosis in VECs with elevated intracellular ROS levels [39,40]. Intracellular ROS levels are regulated by the balance between ROS generation and antioxidant enzymes [41]. Our results showed that elevated ROS levels induced by oxLDL were decreased significantly with PT pretreatment.…”
Section: Discussionsupporting
confidence: 60%
“…Several studies have enumerated the role of ellagic acid in effective lowering of plasma lipids, reduced oxidative stress, inhibition of apoptosis, scavengers of oxygen and hydroxyl radicals as well as inhibition of lipid peroxidation both in vitro and in vivo. It has been known to inhibit the cytokine induced ROS generation and expression of adhesion molecules as well as prevention of oxidized low Density Lipoprotein (LDL) induced apoptosis in the endothelial cells (Lee et al, 2010). The role of T. chebula in inhibiting ROS production may be attributed due to the symbiotic effect of these two important marker compounds present in the extract.…”
Section: Discussionmentioning
confidence: 99%
“…This in turn reduced local expression of cytokines like TNF-α and consequently may attenuate the potentiation of the intramyocardial inflammatory reaction. Hyperglycaemia (Li et al 2010a;Piga et al 2007), oxidised LDL (Lee et al 2010) (Hodgkinson et al 2008;Peterson et al 2007), and increased angiotensin II (Alvarez et al 2004;Rius et al 2010) under diabetes mellitus upregulate the expression of VCAM-1/ICAM-1. Since HDL did not affect blood glucose levels, the reduction in adhesion molecule expression was not an indirect consequence of an HDL-mediated antidiabetic effect.…”
Section: Human Apo A-i Gene Transfer Reduces Diabetes-induced Cardiacmentioning
confidence: 99%